Case Study Research and Applications: Design and Methods - Yin, Dr Robert K. (SAGE Publications, Inc, 2018)
Winner of the 2019 McGuffey Longevity Award from the Textbook & Academ ic Authors Association (TAA) Recognized as one of the most cited metho dology books in the social sciences, the Sixth Edition of Robert K. Yi n's bestselling text provides a complete portal to the world of case s tudy research. With the integration of 11 applications in this edition , the book gives readers access to exemplary case studies drawn from a wide variety of academic and applied fields. Ultimately, Case Study R esearch and Applications will guide students in the successful use and application ofthe case study research method.